A study of the kaolin electro-osmotic consolidation characteristics and their numerical simulation - Meilan SHEN; Taiquan ZHOU; Wugang LI (Shuiwen dizhi gongcheng dizhi, 2021)
Electro-osmotic consolidation is an effective way to promote consolidation of soft soil with low permeability. In order to investigate the basic law of electro-osmotic consolidation behavior of soft clay under different potential gradients, electro-osmotic tests are carried out for kaolin with a self-made device. Changes of current, displacement, settlement and potential with time are measured during the tests, and energy consumption per unit drainage is also analyzed. Based on the electro-osmosis consolidation coupling governing equations, the electro-osmosis of soil consolidation full coupling analysis of finite element programs is developed. The finite element program is developed to examine the fully coupled soil electro-osmotic consolidation behavior based on the multi-field coupling governing equations of electro-osmotic consolidation. The numerical analysis is in good agreement with the analytical results, which proves the efficiency of the program. To predict the settlement of soft clay with time under different potential gradients, numerical analysis is performed to study the electro-osmosis consolidation tests of kaolin clay under three potential gradients: 0.5, 1.0 and 1.5 V/cm, respectively. Numerical simulation analysis for the surface subsidence distribution model, the space-time development of anode excess pore water pressure, and the degree of consolidation of the anode are performed. The numerical analysis results for the settlement are in good agreement with those obtained from the experiments. The results can provide theoretical guidance for practical electro-osmosis tests.